Pre-Service English Teachers’ Experiences in Joining Kampus Mengajar Program - Fayza, Siti Alya; Daud, Afrianto; Masyhur (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Kampus Mengajar is part of Merdeka Belajar-Kampus Merdeka (MBKM) initiatives introduced by the Minister of Education and Culture of the Republic of Indonesia in early 2020. The objective is to enhance the quality of university graduates, enabling them to thrive in the era of the Industrial Revolution 4.0 and Society 5.0. Additionally, the program aims to elevate the professionalism of students aspiring to become teachers. The aim of this research was to explore the experiences of pre-service English teachers in joining this program. This study employed a qualitative method with a narrative approach. Eight students of the English Education Study Program at a university in Indonesia participated in Kampus Mengajar were interviewed. They were selected using a purposive sampling technique. The data were collected through interviews and documentation. The analysis of the data resulted in the identification of four themes. These themes encompassed the motivation for participating in Kampus Mengajar program, the various types of activities undertaken, the lessons gained from teaching and non-teaching activities, and the skills that were improved throughout the program. Based on the results of this study, the participants shared remarkably similar experiences aiming to enhance their skills as university graduates and prospective teachers.